The Analysis of Language Used in “Pluto Projector” Rex Orange County Song - Angelica, Ribka Caroline (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study focused on analyzing language used in “Pluto Projector” Rex Orange County song. The theory used in this study is proposed by Wardhaugh which there are eight types of language. Thedata were collected by identify the type of language and the function of the language based on the meaning of each lyrics on the song. The “Pluto Projector” song was wrote by Alex O‟Connor that inspired by wonders if he truly enough for his partner. This song was full of guitar instrumental that build-up to explain the meanings of the lyrics. This song focused on how to understand the meaning of being life. Therefore, it can be concluded that “Pluto Projector” song used a different types of languge that Alex O‟Connor used to expressed himself because he is a main character in this song who is confused about his life and his relationship, especially when stating his opinion.